The influence of marketing mix on repurchase intention for eco-friendly products among university students in Indonesia - Hadi, Antonius Satria (PHINISI, 2025)
This study examines the impact of marketing mix dimensions on repurchase intention for eco-friendly products among university students in Yogyakarta, Indonesia. Using a quantitative approach, data were collected from respondents through structured questionnaires and analyzed via multiple linear regression. The results indicate that product quality, competitive pricing, and promotional efforts significantly influence repurchase intention. However, distribution channels did not have a significant effect, suggesting that accessibility alone does not drive repeat purchases intention. These findings highlight the importance of product innovation, price optimization, and strategic promotions in encouraging sustainable consumption. This study contributes to green marketing by providing empirical insights into consumer behavior. Future research should explore additional factors such as environmental awareness and brand loyalty to further understand repurchase intentions for eco-friendly products.